(untitled) (Itinera, 2020)
Kant and Hegel have diametrically opposed views concerning the relationship between colour and drawing. For Hegel colour is all; while for Kant drawing is central. Through an analysis of both these positions the conclusion that is drawn is that colour and drawing have a necessary interrelation. One cannot be thought other than in relation to reach other. Taken together they are integral to the development of a philosophy of art.